Relationship Between Money Market and Economic Growth in Nigeria - Bashir Ahmad Daneji (Indonesian Journal Of Business And Economics, 2021)
AbstractThis paper investigated the relationship between money market and economic growth in Nigeria.  Secondary data for 38 years covering the period of 1981 to 2018 was used. Econometric methods of analysis of Lag Length Selection Criteria, ARDL Bound Test for Cointegration, Long Run and Short Run Estimations and Diagnostics Tests of Serial Correlation, Hetroskedascitity, Cusum Test and Ramsey Reset Test were carried out. The result found that there is long run relationship between money market and economic growth, as indicate by the F-statistics 4.48 which is higher than the upper bound values at all level of significance. This suggests that there exists a long run relation between money market and economic growth. The results of the error correction suggest the validity of long-run relationship between money market and economic growth. The study recommends that financial market regulatory body to increase the size of the money market through policy relaxation in order to achieve economic growth in the country.Keywords: Money Market, Economic Growth, Bound Test.JELClassification: C01, E05, G10